A 4-year follow-up of rehabilitation of atrophied edentulous mandible with implant-supported overdenture - Jatin Agarwal; Rolly S Agarwal (Wolters Kluwer Medknow Publications, 2015)
Conventional complete dentures primarily rely on residual alveolar ridge and mucosa for support and retention. Patients with poor mandibular ridge foundation usually suffer from inadequate denture retention and stability. In such cases, implant-supported overdenture treatment provides improved prosthesis retention and support and thus greatly increasing patient's acceptance toward prosthesis as when compared to conventional dentures. The present case report describes a successful rehabilitation of resorbed mandibular ridge with an overdenture supported by two implants.